2005
DOI: 10.1590/s0034-71672005000200011
|View full text |Cite
|
Sign up to set email alerts
|

Dimensionamento de pessoal de enfermagem em um hospital universitário

Abstract: The developed investigation in this type of case study, had as main goal to measure the nursing personnel at a university hospital. The adopted methodology comprizes the identification of some specific variables, among them the patient classification according to the nursing care category and the index of the predicted and not predicted absences. The medical clinic admission and surgical units were studied. Results demonstrated that the current nursing personnel corresponds to 50% of what was expected, whereas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0
40

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 2 publications
2
8
0
40
Order By: Relevance
“…A gravidade deste problema aumentou após a reforma do Estado, tendo em vista que esta definiu como diretrizes básicas a redução de despesas, principalmente do quantitativo de funcionários públicos (responsabilidade fiscal), propiciando, dentre outros, efeito imediato na política de recursos humanos em saúde, que trouxe dificuldades assistenciais e gerenciais, afetando diretamente o quantitativo de pessoal nas instituições hospitalares. 2 Mundialmente, os trabalhadores da saúde constituem uma categoria profissional numerosa e diversificada que precisa ser valorizada. No entanto, inversamente a outros meios de trabalho, o sistema de saúde tem demonstrado tardiamente seu interesse pelos conteúdos de cargas de trabalho, obrigações e riscos a que estão expostos os trabalhadores, bem como sua capacidade de suportar as dificuldades decorrentes da atenção àqueles que são objeto de seu cuidado.…”
unclassified
“…A gravidade deste problema aumentou após a reforma do Estado, tendo em vista que esta definiu como diretrizes básicas a redução de despesas, principalmente do quantitativo de funcionários públicos (responsabilidade fiscal), propiciando, dentre outros, efeito imediato na política de recursos humanos em saúde, que trouxe dificuldades assistenciais e gerenciais, afetando diretamente o quantitativo de pessoal nas instituições hospitalares. 2 Mundialmente, os trabalhadores da saúde constituem uma categoria profissional numerosa e diversificada que precisa ser valorizada. No entanto, inversamente a outros meios de trabalho, o sistema de saúde tem demonstrado tardiamente seu interesse pelos conteúdos de cargas de trabalho, obrigações e riscos a que estão expostos os trabalhadores, bem como sua capacidade de suportar as dificuldades decorrentes da atenção àqueles que são objeto de seu cuidado.…”
unclassified
“…At the same institution, in a five-year period, the percentages varied from 0.2% to 13.5% for nurses, and from 0.9% to 21.9% for technicians/auxiliaries (14) . At medical and surgical hospitalization units of a hospital in western Paraná, the percentage of these absences varied from 6.9% to 9.7% for nurses and from 6.2% to 11.4% for technicians/auxiliaries (10) ; At Hospital São Paulo, located in the city of São Paulo, the variation of these percentages in 40 hospitalization units ranged from 0.5% to 15.7% for nurses, and 0.7% to 12.4% for technicians/auxiliaries (11) .…”
Section: Unplanned Absencesmentioning
confidence: 99%
“…Studies about nursing staff dimensioning, developed by several authors (5,7,(10)(11)(12)(13)(14)(15) in different institutional realities, found variable Technical Safety Indexes (TSI), such as: between 6.9% and 76% for the nurse category, and between 10.38% and 62% for nursing technicians and auxiliaries, which shows the influence of institutional specificities on absenteeism percentages. These results point to the need for further studies about this theme so as to represent the particularities of each institution (5) .…”
Section: Introductionmentioning
confidence: 99%
“…There are several studies about patient classification. However, the focus is on development (12)(13) and instrument validation (14) and/or characterization of the client profile at a given hospitalization unit, including nursing staff dimensioning (15)(16) . Even though the patient classification instrument is considered an important tool for nursing care planning, few studies have explored this segment.…”
Section: Introductionmentioning
confidence: 99%